PENGARUH ATRIBUT PRODUK ROTIBOY TERHADAP KEPUASAN KONSUMEN DI MALL CIPUTRA SEMARANG - Rosalia, Shelli; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2016)
One of the dominant factors for providing customer service is the satisfaction of consumers. Efforts must be made to satisfy customer needs profitably (win-win), the state in which both sides feel to win and no one harmed. Preservation of customer satisfaction with the company's sales volume is expected to be maintained, and even increased. Allegedly the factors that influence consumer satisfaction in this study, among others; affordability, product quality, product design and product reliability.The theory is used to generalize is as stated by Dutka (2010) which says that the product attributes of customer satisfaction are universally include 1) the value price relatons, 2) product quality, 3) product benefits, 4) product features, 5) product Deign, 6) product reliability and consistency, and 7) range of product or service. Dutka signal taken from the 4 factors of product attributes that are considered influential on consumer satisfaction Rotiboy, for reasons related data avaibilitas and visibility of the object, namely; affordability, product quality, product design and product reliability. Thus, the hypothesis is "a positive influence variables affordability, product quality, product design and reliability of the product simultaneously on consumer satisfaction Rotiboy".The research sample of 100 respondents drawn from consumers who shop at Rotiboy Mal Ciputra Semarang, who previously made provision sample size calculation formula Slovin. Sampling using accidental sampling technique. With the tempo of deployment questionnaire that takes about 20 days, then the 100th questionnaire further processed and analyzed.Based on statistical calculations with SPSS, then the inference is variable affordability, product quality, product design and reliability of products collectively or partially, affects customer satisfaction (Y). Thus H1 through H5 is received at the level of 95 percent. Referring to the research results of the four independent variables the study, the four independent variables of research, namely affordability, product quality, product design and reliability of products contributing to customer satisfaction is still possible to be improved, in which the variable quality of products has the most dominant influence on consumer satisfaction.